Brain network mechanism on cognitive control task in the elderly with brain aging: A functional near infrared spectroscopy study - Liang, Junjie; Huang, Jiali; Luo, Zhiwei; Wu, Yuxi; Zheng, Lingxiong; Tang, Zengquan; Li, Wanying; Ou, Haining (Frontiers in Human Neuroscience, 2023)
Objective: To study the brain network mechanism of cognitive control in the elderly with brain aging. Methods: 21 normal young people and 20 elderly people were included in this study. Mini-mental State Examination and functional near-infrared spectroscopy (fNIRS) synchronous judgement test were performed on all subjects. The behavioral data and functional connectivity strength of bilateral prefrontal cortex and primary motor cortex were compared between the two groups. Results: In the forward and reverse judgment tests, the reaction time of the elderly group was significantly longer than the young group (P < 0.05), and there was no significant difference in the correct rate. In the homologous ROI data, the FC of PMC and PFC in the elderly group was significantly decreased (P < 0.05). In the heterologous ROI data, except for LPMC-LPFC, the other PMC and PFC of the elderly group were significantly lower than the young group (P < 0.05) while processing the forward judgment test. However, the heterologous ROI data of LPMC-RPFC, LPMC-LPFC and RPFC-LPFC in the elderly group were significantly lower than the young group (P < 0.05) while processing the reverse judgment test. Conclusion: The results suggest that brain aging affected degeneration of whole brain function, which reduce the speed of information processing and form a brain network functional connection mode different from that of young people.